(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
The identification of species based on anatomical characters is valuable to investigate their taxonomic status, phylogeny and understand their autoecology. The current study analysed the stem and leaf properties of 20 species of the subgenus Cyanus (Mill.) Hayek in Turkey. The Cyanus species exhibited xeromorphic anatomical features, such as tight palisade parenchyma and induced spongy parenchyma, which indicated adaptations to the arid soil and a forest ecosystem in which they occurred, as well as to high light intensity and precipitation. Anatomical features such as the midrib shape and number of vascularization patterns differed among the species. Similar anatomical characters were analysed for the investigated species. These properties can provide an important database for future studies including the phylogeny within the subgenus Cyanus. Bangladesh J. Plant Taxon. 28(2): 295-309, 2021 (December)